DERMATITIS KONTAK AKIBAT KERJA PADA PEKERJA GARMEN - I Made Stepanus Biondi Pramantara; I Made Brathiarta (Universitas Udayana, 2014)
Occupational contact dermatitis is a dermatitis that occurs due to contact with thematerials that exist in the workplace, and this is not the case if the person does not work.In the textile workers, the incidence of occupational contact dermatitis ranks fourth ofall occupational skin diseases annually in Finland. Contact dermatitis is of two kinds,namely contact dermatitis (DKI) arising through non-immunologic mechanisms andallergic contact dermatitis (DKA)as a result of specific immunologic mechanism (slowtype hypersensitivity reaction (type IV)). To assign a material cause of contactdermatitis required a careful history taking about, a complete medical history, physicalexamination and patch test and is also required investigation into the workplace toobserve the work and what materials are usually in contact with the patient when thepatient works. Some of the materials most commonly cause dermatitis due to work ingarment workers are resins, formaldehyde and dyes. Handling contact dermatitis can bedivided into non-pharmacological therapy and pharmacology. The best way toovercome work-related contact dermatitis is prevention by avoiding contact of thematerial causes. Long-term prognosis of occupational contact dermatitis is very bad,despite the best efforts of treatment and change the type of work has been done.